On the issue of forming the properties of restoration compositions based on air and hydraulic binders - P. D. Bataeva; Z. Z. Alarhanova; Kh. M. Bataeva; A. D. Bataev (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. This study provides a review of organic additives, organic and inorganic binders, including air and hydraulic lime binders. Heat and mass transfer in the processes of decarbonization and carbonization of air and hydraulic lime binders and repair and restoration compositions based on them is considered, knowledge of which is necessary for the design of equipment and technological processes for the production of mineral binders, as well as technologies and compositions for repair and restoration work. Method. The dissociation and decarbonization reactions are given as reversible reactions, the decomposition front, the boundaries of limestone decomposition, the dissociation time and the dissociation reaction rate are calculated. To obtain complete information on mass transfer during the decarbonization of limestone, heat transfer is also taken into account, which complicates the task due to the nonisothermal temperature field, which affects the difference in the rates of the decarbonization reaction. Result. The solution of the problem, carried out by Held and Ivanov, and the Fourier differential equation of thermal conductivity are given. The types of lime hardening are considered: carbonate, hydrate and hydrosilicate. Carbonate hardening of lime is presented as a hardening process that takes a long time. The mechanism of carbonate hardening has been studied. The dependence of carbonization intensity on water content and humidity was revealed. Conclusion. The scientific and practical value of a new scientific direction has been established: “Research of air and hydraulic lime binders and the development of repair and restoration compositions based on them.” As a result of the research, new compositions have been developed for the repair, restoration and restoration of historical and cultural monuments that meet the repair and restoration requirements.